A Comprehensive Systematic Review of Antimicrobial Resistance in Community - Acquired Infections Managed in Primary Health Care - Agsion Marce Kombongan (International Medical Journal Corp. Ltd, 2025)
Introduction: Antimicrobial resistance (AMR) in community-acquired infections presents a critical global health threat, disproportionately affecting primary healthcare settings where most antibiotics are prescribed. Despite two decades of stewardship efforts, antibiotic prescribing rates remain persistently high, and resistance patterns show alarming geographic and temporal trends. This systematic review synthesizes the current evidence on the prevalence, clinical impact, drivers, and management of AMR in community-acquired infections within primary care. Methods: We conducted a comprehensive systematic review following established guidelines. We screened studies based on predefined criteria focusing on community-acquired bacterial infections, primary healthcare settings, and AMR data. Data from 80 included studies were extracted across domains including study setting, pathogens, resistance methodologies, findings, associated factors, and intervention outcomes. Studies encompassed systematic reviews, randomized trials, observational studies, and quasi-experimental designs from diverse global regions. Results: AMR prevalence varies significantly by infection type and geography. In urinary tract infections (UTIs), E. coli resistance to ampicillin was 53.4% in OECD countries versus 79.8% in non-OECD countries. Ciprofloxacin resistance is rising in community-acquired UTIs (P=0.003). For respiratory tract infections, pneumococcal penicillin non-susceptibility reached 58% in some regions, though amoxicillin susceptibility remains preserved in many areas. Antibiotic-resistant infections lead to worse clinical outcomes, particularly in UTIs (OR 4.19 for clinical failure), increased healthcare utilization, and higher economic costs. Antibiotic exposure directly increases individual patient resistance, with effects persisting for up to 12 months. Inappropriate prescribing is pervasive (global pooled estimate 57.6%). Multifaceted antimicrobial stewardship (AMS) interventions, especially those incorporating education, audit/feedback, and decision support, are effective and cost-effective, reducing inappropriate prescribing by 4.2% to 63.69% without compromising patient safety. Discussion: The observed heterogeneity in resistance rates stems from differential antibiotic access policies, healthcare utilization patterns, and dynamic temporal evolution. The discrepancy in clinical impact between UTIs and respiratory tract infections is explained by the differing self-limiting nature of these illnesses and variations in empiric therapy efficacy. The persistence of resistance post-exposure varies by antibiotic class, influenced by the fitness costs of resistance mechanisms. Successful interventions must be context-specific, targeting high-prescribing settings with intensive, multifaceted programs. Conclusion: AMR in primary care is a complex, evolving challenge marked by stark global disparities. The direct link between antibiotic prescribing and individual-level resistance underscores the urgency of optimizing prescribing. Evidence-based, context-adapted AMS interventions are effective and should be widely implemented. Future efforts must prioritize equitable diagnostic access, shorter antibiotic courses, and ongoing surveillance to guide empiric therapy and steward our remaining antimicrobial arsenal.